The victimization of women law, policies, and politics - Meloy, Michelle L.; Miller, Susan L. (New York ; Oxford : Oxford University Press, 2011)
In this work, Michelle Meloy and Susan Miller present a balanced, comprehensive, and objective summary of the most significant research on the victimizations, violence, and victim politics that disproportionately affect women.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Women -- Crimes against; Women -- Violence against; Victims of crimes; Victims of violent crimes